Etnomatematik dan Bahasa Melayu - Mohammad Alinor Abdul Kadir (Universiti Kebangsaan Malaysia, 2005)
In his paper “Pembangunan Sains Matematik Mengikut Acuan Malaysia” presented at a colloquium organized by Pusat Pengajian Sains Matematik on 14th March 2000, Shaharir Mohamad Zain highlighted seven issues on how Malaysian mathematicians should contribute towards the development of mathematical science. His main arguments are not free from cultural values. Two of the seven issues are on the early development of mathematical science evolving from Malay value, namely Bahasa Melayu. This paper attempts to elaborate these two aspects